Local heating in the growing of winter vegetables - Jože OSVALD; Avgust VRŠČAJ (Acta Agriculturae Slovenica, 1998)
The experiment deals with the comparison of different microclimates and the growth development of lettuce (cv.’Donia’ and cv. ‘Aprilia’), spinach (cv.’Matador’) and corn salad (cv. ‘Holandski’) in two tunnels with different local heating (tunnel A - the heating pipes were placed 20 cm deep in the soil, tunnel C - the heating pipes were placed on the surface of the soil, between rows) and in an unheated tunnel (B). The trial took place on the experimental field of the Biotehnical Faculty in Ljubljana from Dec. 1992 to Mar. 1993. With the lowest air temperature (20 cm above the soil) -6.5 °C, the air temperature in C was -2.5 °C,  in A -4.5 °C, and in B -6.8 °C, the temperature of the soil at a depth of 5 cm was 8.5 °C in A, 1 °C in B, and 3 °C in C. The entering temperature of the heating water was between 24 ° and 27.5 °C; the thermal - current from the surface of the heating pipes into their surrounding was 54 W/m2 in A and C 38 W/m2 of soil surface. The analyses of growing and yield show that the heaviest and most developed vegetables were in A and the least developed in B. All the vegetables had a long growing period because of the low morning and night air temperatures in the tunnels. This fact proves that none of the experimented forms of local heating is adequate as independent heating for growing winter vegetables. These experimental forms can be used only as supplementary heating.